Social Media as Political Party Campaign Media in the 2020 Elections of Maros Regency (Study on the Use of Social Media Instagram Chaidir Syam-Suhartina Bohari Elected Social Media) - Ummah Suhaimah, Alfiah; Iqbal Sultan, Muh.; Arianto, Arianto (Journal Research of Social Science, Economics, and Management, 2022)
Internet has penetrated not only urban areas but also remote villages, and has become a necessity for society as a whole. The spread of the internet has become a common thing in changing the social order of society. This study aims as a means of communicating information delivery through social media Instagram. This study uses a qualitative approach with literacy techniques. In the past, literacy referred to a person’s ability to process and understand information in the process of reading and writing. Utilization of social media Instagram as a promotional medium by the elected regent pair. Instagram social media is used as a communication medium to communicate profiles, activities and information about partner selection. The results of this study indicate that the use of Instagram social media has not been optimally used by the chairman pair Syam-Suhartina Bohari because there is no special board to manage it.